Biscuit, cracker, and cookie recipes for the food industry - Manley, D. J. R. (Duncan J. R.), 1938- (Woodhead Publishing series in food science and technology., 2001)
Duncan Manley has over thirty years' experience in the biscuit industry and during this period has collected recipes and examples of best practice from the leading manufacturers of biscuit, cracker and cookie products throughout the world. In his new book Manley has put together a comprehensive collection of over 150 recipes to provide technologists, managers and product development specialists with a unique and invaluable reference book. Development activity is essential for all companies but it is potentially very expensive. This unique new book will enable research and development staff to benefit from the experiences of other manufacturers in new product development. It also provides an invaluable resource for production managers who wish to investigate improvements and cost reductions for existing lines. The book begins by investigating some of the key variables in effective recipe development. It then presents a series of recipes for hard-dough products such as crispbread and crackers, short-dough biscuits and cookies, extruded and deposited dough products. Further chapters include recipes for sponge biscuits, wafers and secondary processes such as icing and chocolate coating. A final chapter covers the important area of dietetic products, including recipes for reduced fat and sugar biscuits and products for particular groups such as diabetics and babies. Biscuit, cracker and cookie recipes for the food industry provides unparalleled access to best practice in the industry, and a wealth of ideas for product developers and production managers. It will be an essential resource. Take advantage of over thirty years of industry experienceCompare your recipes with over 150 included in this book - improve, refine and experimentEnhance your product development process with sample recipes from all areas of this industry including cream crackers, pretzels, sponge drop biscuits, plain biscuits, wafers and secondary processing products such as icing, jam, marshmallow and chocolate.